Tpack implementation in literature learning: Perceptions of high school students in Indonesia - Nofitria, Anri; Suwandi, Sarwiji; Sumarwati, Sumarwati (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the implementation of Technological Pedagogical Content Knowledge (TPACK) in high school literary education and examines students’ perceptions of integrating technology into learning. The advancement of digital technology has led to the incorporation of tools such as PowerPoint, digital reading, theatre films, Google Drive, and WhatsApp in literature education. This research, involving 106 students from three high schools in Surakarta, used a mixed-method approach combining quantitative and qualitative data. The results show that TPACK positively impacts students’ comprehension, engagement, and learning productivity. However, challenges such as limited access to technology and information management issues must be addressed for more effective TPACK implementation in the future. The study suggests improving technology access, developing curricula that blend technology with traditional methods, and providing teacher training for its effective integration. It also highlights the need for better technological infrastructure in schools to ensure equitable access to digital resources for all students. This study offers valuable insights for creating curricula and policies to enhance the integration of technology in literacy instruction, ultimately improving students’ engagement and comprehension of literary texts in Indonesia.